2023
DOI: 10.5194/hess-27-837-2023
|View full text |Cite
|
Sign up to set email alerts
|

Past and future climate change effects on the thermal regime and oxygen solubility of four peri-alpine lakes

Abstract: Abstract. Long-term effects of climate change on lakes globally will include a substantial modification in the thermal regime and the oxygen solubility of lakes, resulting in the alteration of ecosystem processes, habitats, and concentrations of critical substances. Recent efforts have led to the development of long-term model projections of climate change effects on lake thermal regimes and oxygen solubility. However, such projections are hardly ever confronted with observations extending over multiple decade… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…The simulated results are comparable to the climate change simulations performed by Desgué‐itier et al. (2023), who also found that an increase of around 2°C for surface water temperature in Lake Geneva can be anticipated for year 2060 under RCP8.5 climate conditions. This scenario assumed that the current greenhouse emission situation will remain and no significant measures are taken to alleviate climate change, which has been a typical scenario to consider for the simulations till the middle of the 21st century.…”
Section: Discussionsupporting
confidence: 85%
“…The simulated results are comparable to the climate change simulations performed by Desgué‐itier et al. (2023), who also found that an increase of around 2°C for surface water temperature in Lake Geneva can be anticipated for year 2060 under RCP8.5 climate conditions. This scenario assumed that the current greenhouse emission situation will remain and no significant measures are taken to alleviate climate change, which has been a typical scenario to consider for the simulations till the middle of the 21st century.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, since the 1950s, it has experienced a history of anthropogenic eutrophication followed by re-oligotrophication similar to that of several other lakes over about the same time period 11 . And like other lakes, Lake Geneva faces the ongoing effects of climate change with signi cant warming trends and strengthening thermal strati cation 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Given the projected worldwide increase in strati cation intensity and duration of deep lakes as a response to climate warming [24][25][26] , prolonged isolation of the hypolimnion from the atmosphere is expected. As a result, lakes will be increasingly susceptible to hypoxia because of less frequent mixing with more severe consequences expected for the systems with a eutrophic past.…”
Section: Hypoxia Under Future Climate Changementioning
confidence: 99%
See 2 more Smart Citations